A Review of the Bulgaria School Autonomy Reforms - World Bank (Washington, DC, 2013)
The sweeping decentralization reform of the education system introduced by the Government in 2007 to promote greater school autonomy and more efficient spending produced impressive efficiency gains and set the foundation for better adjustment to local needs. Despite initial successes, lingering concerns remain about the accountability of schools to the local community. Thus, as a part of a continued engagement with the Government of Bulgaria, this study records the achievements of the reforms and highlights outstanding challenges. Its aim is to assess progress in the functioning of the model of delegated financing and governance in the education sector. The study aims to identify where the model could be strengthened to further improve the achievement of the objectives of the reform. The study focuses on four questions: (1) To what extent are the reforms leading to a more efficient system? (2) Is there any evidence that the quality of education had been impacted by these reforms? (3) What is the equity impact of the school closures? (4) How are accountability mechanisms affecting the role of the major stakeholders?